Purification of functional, determinant-specific, idiotype-bearing murine T cells - Lewis, GK (The Rockefeller University Press, 1978)
Strain A/J mice immunized with azobenzenearsonate (ABA)-mouse IgG conjugates develop suppression for anti-trinitrophenyl(TNP) responses to doubly conjugated (ABA,TNP) proteins. This suppression is specific for the ABA epitope and is mediated by T cells in cell transfer experiments. ABA-binding T cells from suppressed animals were purified by a two-stage procedure in which B cells were removed from spleen cell populations by adherence to plastic surfaces coated with anti-mouse Ig antibody, followed by binding the nonadherent population (more 95 percent Thy-1-positive) to surfaces coated with ABA-protein conjugates. Approximately 90 percent of the cells recovered by temperature-dependent elution from the ABA plates (similar to 2 percent of the spleen cells) bound antigen immediately afterward, and up to 50 percent of the cells bound anti-cross-reactive idiotype antibody. On the other hand, the nonadherent T-cell population was completely negative in the antigen- binding and idiotype assays. Another distinguishing feature of the two T-cell populations was that 78 percent of the adherent cells, but only 2 percent of the nonadherent cells, were Ia positive, although the specific I-region marker(s) expressed on the cells was not identified. The biological function of the antigen-binding T cells was investigated using a standard cell transfer protocol. Suppressor cells were enriched in the adherent population by a factor of at least 25, establishing that functional, epitope-specific, idiotype-bearing T cells can be significantly purified by this procedure. Note Added in Proof. We have recently isolated two types of ABA-binding molecules biosynthetically labeled with (35)S-methionine from NP-40 lysates of purified antigen-specific T cells. The molecules were purified by adsorption onto an ABA-Sepharose immunoadsorbent followed by elution with 9 M urea. Autoradiograms of SDS-PAGE of the eluates revealed components with tool wt of approximately 60,000 and 33,000 dahons. These molecules were not present in eluates from a bovine IgG-Sepharose control immunoadsorbent and thus represent specific ABA-binding products synthesized by T cells.